Effects of Interannual Environmental Changes on Juvenile Fish Settlement in Coastal Nurseries: The Case of the Adriatic Sea - Matić-Skoko, Sanja; Vrdoljak, Dario; Uvanović, Hana; Pavičić, Mišo; Tutman, Pero; Bojanić Varezić, Dubravka; Kovačić, Marcelo (Frontiers in Marine Science, 2022)
This study tested generality in the settlement and recruitment patterns of juvenile fish in the coastal Mediterranean as driven by interannual environmental differences. A multivariate analysis of juvenile fish community data, sampled over three consecutive years, was conducted to elucidate the interannual changes of new settlers’ occurrence and abundance in different nurseries along the eastern Adriatic coast. Sites were assigned to four groups of nurseries based on water type (marine or transitional) and geographical position (north or south). Statistically significant interannual differences were found in temperature but not in salinity. In general, species occurrence significantly fluctuated between years and seasons. The highest total abundance of juveniles was observed in the significantly warmer year 2018 within all study groups. Defined groups expressed significant annual differences in species richness and abundance related to variations in water temperature and salinity as environmental factors for the same consecutive years. Nurseries within transitional waters in the north are more prone to interannual water temperature changes. The associated community composition differed most from those recorded in southern marine waters, where groups were mostly defined by salinity influence and were least sensitive to interannual temperature fluctuations. The cold and rainy spring in 2019 caused late settlement and longer retention of specific economically and ecologically important fish species in the nurseries. The results suggested that settlers’ delay or retention due to negative temperature deviation in the spawning period were linked to the nurseries located in the northern transitional waters that are under a stronger coastal influence. These delays can have ecological consequences on population dynamics and on inter- and intraspecific relationships within specific nursery communities.